Brazilian identities: compositions and recompositions - Rodrigues, Cristina Carneiro [UNESP]; Luca, Tania Regina de [UNESP]; Guimarães, Valéria; Moreno, Jean Carlos; Flores, Maria Bernadete Ramos; Melo, Sabrina Fernandes; França, Jean Marcel Carvalho [UNESP]; Viotti, Ana Carolina de Carvalho [UNESP]; Isaia, Artur Cesar; Anhezini, Karina [UNESP]; Ferreira, Ricardo Alexandre [UNESP] (Cultura Acadêmica, 2015)
The Contemporary Challenges series - originally sponsored by the Research Deanship of the State University of São Paulo (Unesp) - aims at providing access to essays on crucial issues concerning the Brazilian society as a whole. With the publication of those titles, which systematically avoid unnecessary academic jargon though preserving scientific rigour, the university fulfills one of its essential tasks: that of disseminating the skills and knowledge reared within its quarters. In the present volume, focused upon sociological questions, the authors face the difficult job of grasping the intricate horizon of complexities of Brazilian identity and their presence in the current national dilemmas.
Keywords: Sociologia - Brasil; Identidade Social - Brasil; Cultura política - Brasil